DIGITAL LITERACY-BASED MARKETING MANAGEMENT STRATEGY TO INCREASE STUDENT ENTREPRENEURSHIP PRODUCT PURCHASE INTEREST AT SATYAGAMA UNIVERSITY - Didi Sukardi; Rahmatullah Rahmatullah; I Nyoman Suri Adnyana; Murdiyono Murdiyono (Yayasan Nusantara Hasana Berdikari, 2024)
The development of digital technology has transformed the marketing patterns of student entrepreneurial products into more modern and digital-based media. This study aims to analyze digital literacy-based marketing management strategies to increase consumer interest in purchasing student entrepreneurial products at Satyagama University. The research method used a quantitative approach through the distribution of questionnaires to Satyagama University students involved in entrepreneurial activities. The results show that digital literacy skills, social media utilization, and digital marketing strategies have a positive influence on increasing consumer interest in purchasing student products.